ENHANCE CATALOGIZED SYSTEM INFORMATION IN THE LIBRARY, ARCHIVES AND DOCUMENTATION OF DISTRICT SOUTH TAPANULI - Heni Wulandari (INFOKUM, 2021)
Whereas South Tapanuli students used the Willem Iskandar Regional Library as a source of teaching and learning, it was found that not many used the library. Whereas Padangsidimpuan students in visiting or borrowing books to the Willem Iskandar Regional Library, the researchers saw from the list of borrowed books, sometimes only 6 people borrow books a week and sometimes they don't exist at all, sometimes even in doing homework (PR) students are more often choose to use the Internet, because they think it is easier and faster. This shows that the low interest of MAN 1 Padangsidimpuan students in using the library as a source of learning. It should be learned not only in the study room, but it is very important to develop knowledge by reading a lot of books in the library. And the inhibiting factors for student interest are low student interest in reading, the location of the library is too far from the classroom, facilities in the library very limited, library collection that uses a lot of old books..